تقييم نموذج Eckel المستخدم في كشف ممارسات تمهيد الدخل (دراسة تطبيقية على الشركات المساهمة الصناعية في الأسواق المالية العربية) - مكية نغم; مرتكوش عمار (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف البحث إلى تقييم نموذج Eckel المستخدم في كشف ممارسات تمهيد الدخل، من خلال دراسة أثر تغير مدخلات النموذج Eckel على نتائج النموذج في كشف تمهيد الدخل لتحديد مزايا وعيوب النموذج، وتوصل الباحث إلى النتائج التالية: لا توجد علاقة ذات دلالة إحصائية بين نتائج الطرق المستخدمة لكشف تمهيد الدخل بالاعتماد على مجمل الدخل ونتائج الطرق المستخدمة لكشف تمهيد الدخل بالاعتماد على صافي الدخل التشغيلي، لا تختلف نتائج نموذج Eckel باختلاف طول السلسلة عند سنة ثابتة كما أنها تكون متماثلة عندما نأخذ السلسة كاملة، تختلف نتائج نموذج Eckel باختلاف بيانات الدخل ( مجمل الدخل أو صافي الدخل) عند سنة ثابتة إلا أنها تكون متقاربة عند دراسة السلسلة كاملة، ويدل تقارب نتائج تمهيد الدخل للشركات الصناعية باستخدام بيانات مجمل الدخل وصافي الدخل التشغيلي على إصرار إدارة الشركات على تمهيد دخلها. The research aims to Evaluate the Eckel model used in detecting income smoothing practices, Through study the effect of changing the model inputs practices Eckel on the results of the model to pave the income to determine the advantages and disadvantages of the model revealed, and the most important results: There were no statistically significant differences between the methods used the results to detect Income Smoothing relationship Depending on the total income and the results of the methods used to detect Income Smoothing based on net operating income, the results of model Eckel does not vary depending on the length of the string at year fixed and it be the same when we take the whole series, the results of model Eckel vary according to income statements (total income or net income) year fixed when they are close together when the full study series, shows the convergence Income Smoothing of industrial companies using the total income and net operating income data on the insistence of corporate governance to pave the results of their income.